Scenario Development of Wasathiyah-Based Akhlak Tasawuf Learning at The State Islamic University Of North Sumatra - Abdul Karim, Pangulu; Rambe, Andina Halimsyah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
This study aims to obtain a valid and practical wasathiyah-based akhlak tasawuf learning scenario product. The research was conducted at the Faculty of Tarbiyah and Teacher Training (FITK) and the Faculty of Ushuluddin and Islamic Studies (FUSI) State Islamic University of North Sumatra Medan with the participants of akhlak tasawuf lecturers and students of both faculties. The research and development steps are guided by the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. There were two results obtained in this study. First, the learning scenario product was declared very valid in the validity test with a percentage of 90% on design validation and 85.33% percentage on product content validation. Revision I was made based on qualitative data related to design and content based on comments from each validator. Second, the scenario of wasathiyah-based akhlak tasawuf learning was stated to be very practical, as shown in small group trials, which obtained practicality percentages of 87.05% (respondent was one lecturer) and 80% (respondent was seven students). In the large group trial, the average practicality presentation was 89% (7 lecturers respondents) and 90% (21 students respondents), so it was concluded that the learning scenario developed was in the